Clinicopathological, genomic and immunological factors in colorectal cancer prognosis. Issue 2 (17th January 2018) - Marks, K. M.; West, N. P.; Morris, E.; Quirke, P.
Abstract : Background: Numerous factors affect the prognosis of colorectal cancer (CRC), many of which have long been identified, such as patient demographics and the multidisciplinary team. In more recent years, molecular and immunological biomarkers have been shown to have a significant influence on patient outcomes. Whilst some of these biomarkers still require ongoing validation, if proven to be worthwhile they may change our understanding and future management of CRC. The aim of this review was to identify the key prognosticators of CRC, including new molecular and immunological biomarkers, and outline how these might fit into the whole wider context for patients. Methods: Relevant references were identified through keyword searches of PubMed and Embase Ovid SP databases. Results: In recent years there have been numerous studies outlining molecular markers of prognosis in CRC. In particular, the Immunoscore® has been shown to hold strong prognostic value. Other molecular biomarkers are useful in guiding treatment decisions, such as mutation testing of genes in the epidermal growth factor receptor pathway. However, epidemiological studies continue to show that patient demographics are fundamental in predicting outcomes. Conclusion: Current strategies for managing CRC are strongly dependent on clinicopathological staging, although molecular testing is increasingly being implemented into routine clinical practice. As immunological biomarkers are further validated, their testing may also become routine. To obtain clinically useful information from new biomarkers, it is important to implement them into a model that includes all underlying fundamental factors, as this will enable the best possible outcomes and deliver true precision medicine. Abstract : Defines modern practice